2010
DOI: 10.3109/14767050903551509
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 in maternal circulation: An association with preterm labor and preterm PROM, but not with intra-amniotic infection/inflammation

Abstract: Objective Pentraxin 3 (PTX3) is an acute-phase protein that has an important role in the regulation of the innate immune response. The aim of this study was to determine if maternal plasma PTX3 concentration changes in the presence of intra-amniotic infection and/or inflammation (IAI) in women with preterm labor (PTL) and intact membranes as well as those with preterm prelabor rupture of membranes (preterm PROM). Study design This cross-sectional study included women in the following groups: 1) non-pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Each of these pathways is central in the deployment of an inflammatory response: cytokine-cytokine receptor interaction, Jak-STAT signaling, the complement and coagulation pathway, NOD-like receptor signaling, systemic lupus erythematosus (specifically the complement C1q complex), and chemokine signaling. Interestingly, components of these pathways have been previously linked to both normal parturition [57, 75, 76, 159, 180, 201, 213, 221, 226–228, 235, 271, 274, 308] and the “Great Obstetrical Syndromes” [32, 33, 64, 7982, 84, 85, 89, 238, 267, 291, 295, 307, 320], including preterm labor [28, 58, 74, 77, 83, 8688, 119, 120, 164, 165, 211, 223, 246, 252, 254, 290, 292, 293, 316319]. Indeed, our group has reported an association between activation of the NALP3 inflammasome and the common pathway of parturition [119].…”
Section: Discussionmentioning
confidence: 99%
“…Each of these pathways is central in the deployment of an inflammatory response: cytokine-cytokine receptor interaction, Jak-STAT signaling, the complement and coagulation pathway, NOD-like receptor signaling, systemic lupus erythematosus (specifically the complement C1q complex), and chemokine signaling. Interestingly, components of these pathways have been previously linked to both normal parturition [57, 75, 76, 159, 180, 201, 213, 221, 226–228, 235, 271, 274, 308] and the “Great Obstetrical Syndromes” [32, 33, 64, 7982, 84, 85, 89, 238, 267, 291, 295, 307, 320], including preterm labor [28, 58, 74, 77, 83, 8688, 119, 120, 164, 165, 211, 223, 246, 252, 254, 290, 292, 293, 316319]. Indeed, our group has reported an association between activation of the NALP3 inflammasome and the common pathway of parturition [119].…”
Section: Discussionmentioning
confidence: 99%
“…They found the lowest concentrations in women with infection (based on amniotic fluid culture) or with IAI (based on amniotic fluid IL-6 levels). However, the same group did not find differences in levels of pentraxin-3 in maternal plasma [50] between women exposed and not exposed to this infectious/inflammatory condition. Finally, Park et al [51] suggested maternal serum C-reactive protein as an independent predictor of IAI (based on amniotic fluid matrix metalloproteinase-8 levels).…”
Section: Maternal Bloodmentioning
confidence: 93%
“…Recent studies indicate that the highest PTX3 levels in plasma occur during labor [13,14,26]. Moreover, significant differences in plasma PTX3 levels were observed between women with differing types of delivery.…”
Section: Discussionmentioning
confidence: 99%